On the Fate of Aerosols Produced by New Particle Formation in the Upper Troposphere and Lower Stratosphere - R. Ueyama; W. P. Smith; M. Brown; E. J. Jensen; L. Ziemba; T. P. Bui; J. Dean‐Day; C. J. Williamson (Geophysical Research Letters, 2025)
Abstract New particle formation (NPF) in the upper troposphere and lower stratosphere (UTLS) has been suggested to contribute to cloud condensation nuclei in the troposphere, as well as for maintaining the stratospheric aerosol layer over the Asian summer monsoon (ASM). However, the fate of newly formed particles and their potential impact on climate are largely unknown. Here we use in situ aircraft measurements of aerosol size distributions collected in the UTLS over the eastern ASM region, combined with Lagrangian trajectory modeling and satellite‐derived convection, to show that NPF events primarily occur downstream of convection in the upper troposphere (below the tropopause) between 350 and 360 K potential temperature levels. While the majority of air parcels containing NPF events descend into the lower troposphere, approximately 20% of NPF event parcels ascend into the stratosphere and thereby may contribute as a source of material to the stratospheric aerosol layer.